Takotsubo Cardiomyopathy in a Patient with Undiscovered Sigmoid Colon Cancer - Huang Po-Yen; Ku Po-Ming (Case Reports in Cardiology)
Takotsubo cardiomyopathy (TTC) is a stress-related cardiomyopathy that is characterized by reversible left systolic dysfunction, which appears to be precipitated by sudden emotional or physical stress in the absence of myocardial infarction. Here we present a rare case that clinically presented with intermittent abdominal pain, initially impressed as non-ST elevation myocardial infarction and congestive heart failure but with a normal coronary angiogram. Her symptoms relieved spontaneously without returning. Sigmoid colon cancer was diagnosed via colonoscopy later due to persistent abdominal discomfort. In the absence of detectable emotional or physical stress factors, the newly diagnosed sigmoid colon cancer was the only possible trigger factor of TTC. We offer this case as a reminder that cancer should be considered in the differential diagnosis of patients presenting with the etiology of TTC.